2013
DOI: 10.1002/ejoc.201300069
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Oligoamide Foldamers with a “Wet Edge” as Inhibitors of the α‐Helix‐Mediated p53–hDM2 Protein–Protein Interaction

Abstract: This paper describes the design, synthesis and structural analysis of a 3‐O‐alkylated aromatic oligoamide that incorporates an additional hydrophilic 6‐O‐alkyl substituent in the central monomer. This oligomer exhibits low μM inhibitory potency against the p53–hDM2 interaction compared with its unfunctionalised counterpart and significantly improved solubility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 61 publications
0
32
0
2
Order By: Relevance
“…The structure-based design of small molecules that can stabilize or disrupt helix-protein interactions with high specificity and efficacy is a central challenge in medicinal chemistry. Small molecules which can present functional groups on a pre-organized framework have been identified that disrupt the helix-protein recognition surfaces in interactions such as p53/hDM2 (Prabhakaran, Barnard, et al, 2013; Yin, Lee, et al, 2005), Bak/Bcl-x L (Ernst, Becerril, et al, 2003), and the six helix-bundle assembly of GP41 (Ernst, Kutzki, et al, 2002). Plainly, helix-protein interactions are an important and addressable category of biological target.…”
Section: Introductionmentioning
confidence: 99%
“…The structure-based design of small molecules that can stabilize or disrupt helix-protein interactions with high specificity and efficacy is a central challenge in medicinal chemistry. Small molecules which can present functional groups on a pre-organized framework have been identified that disrupt the helix-protein recognition surfaces in interactions such as p53/hDM2 (Prabhakaran, Barnard, et al, 2013; Yin, Lee, et al, 2005), Bak/Bcl-x L (Ernst, Becerril, et al, 2003), and the six helix-bundle assembly of GP41 (Ernst, Kutzki, et al, 2002). Plainly, helix-protein interactions are an important and addressable category of biological target.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to functionalize the non-recognition face of these scaffolds have been described by Wilson and co-workers. [297, 298] However, the improvement in solubility is associated with a concomitant decrease in the inhibitory activity. A dimeric mimetic of N-alkylated oligoamides lacking positive cooperativity has also been synthesized by means of click chemistry.…”
Section: Methodsmentioning
confidence: 99%
“…N‐Alkylierte Oligoamide ( 34 ) sind bisher die strukturell einfachsten Oligoamide. Versuche, die Seite des Strukturgerüsts zu funktionalisieren, die nicht für die Erkennung benötigt wird, wurden von Wilson und Mitarbeitern unternommen 297. 298 Allerdings bewirkte eine Verbesserung der Löslichkeit gleichzeitig eine Absenkung der Inhibitoraktivität.…”
Section: Methodikunclassified